PENGARUH KARAKTERISTIK AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris pada Auditor KAP di Kota Semarang) - Muhammad Rezky Setiapraptadi; Herry Laksito (Diponegoro Journal of Accounting, 2019)
This study aims to analyze the effect of auditor characteristics such as experience, competence, responsibility, objectivity, independence, due professional care, and integrity on audit quality. This research was conducted at Public Accounting Firm Auditors who worked in Semarang. Sampling is done by convenience sampling.This study uses primary data obtained from the distribution of questionnaires to Public Accounting Firm Auditors in Semarang. The number of questionnaires used in this study amounted to 42 questionnaires in 10 Public Accounting Firms.Research results show that competency, responsibility, due professional care, and integrity have a positive effect on audit quality. Whereas experience, objectivity and independence have no effect on audit quality.